Social informatics Third International Conference, SocInfo 2011, Singapore, October 6-8, 2011 : proceedings - SocInfo 2011 (Conferência) (Lectures notes in computer science, 2011)
This book constitutes the proceedings of the Third International Conference on Social Informatics, SocInfo 2011, held in Singapore in October 2011. The 15 full papers, 8 short papers and 13 posters included in this volume were carefully reviewed and selected from 68 full paper and 13 poster submissions. The papers are organized in topical sections named: network analysis; eGovernance and knowledge management; applications of network analysis; community dynamics; case studies; trust, privacy and security; peer-production.